HISTOARCHITECTURE OF SENSORY STRUCTURE IN SKIN OF RABBIT - Chavan, C A; Waghode, H J; Ladukar, Neeta; Ladukar, O N; Nanadeshwar, N S (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
The skin of rabbit consisted highly specialized sensory structure i.e. Tylotrich follicles were present throughout the skin. These follicles were larger than the normal hair follicles. The most prominent sensory structure of Tylotrich follicle were annular complex which consisted of annulus around the capillaries externally, thin band of smooth muscle centrally and nerve fibres internally. The Haarscheibe surrounds the orifice of tylotrich follicle.
Keywords: Histoarchitecture; Sensory Structure; rabbit; Skin